(untitled) (Fiep Bulletin - online, 2014)
Currently the frequency of the otorhinolaryngological diseases is increasing that they can intervene with the social and educational life of a child. Among them the antrochoanal polyp, in its more advanced cases can shake the psychological, educational and social development of the pediatrics patients. The objective of this work is to analyze and to alert concerning the educational and social aspects that this illness can unchain. Patient V.P. of the feminine sex, 5 years of age, with diagnosis of antrochoanal polyp, with obstruction of important superior airway associated the polyp injury extruding previously in nasal cavity left, submitted the surgery and the psychological evaluation. This consisted of anamneses, application of the projective test (HTP) and of the "Child Scale of Quality of Life" (Auto questionnaire Qualité de Vie Enfant Imagé - AUQEI) that they had detached that after the sprouting of the antrochoanal polyp, the patient presented psychological alterations and worsening of the quality of life. Thus, the present work also showed that the antrochoanal polyp has to bring disorders in the social and educational scope, also in the quality of life of the child, where the intervention of the educator is necessary, aiming at the best inclusion and adaptation of this individual in the school.